Conventional Culture Media for the Growth of Microbes Using of Date Palm (Phoenixdactylifera) Pollen Grains (DPPG) - Zahraa Abd-Alrzaq (Journal of Global Pharma Technology, 2018)
Background: Culture media used in the laboratory for the cultivation of microorganism supply the nutrients required for the growth and maintenance. Objectives: The study was conducted to developing alternative media namely DPPG1, DPPG2and DPPG3 by using a cheap locally available materials such as date palm pollen grains (DPPG) instead of high cost artificial media such as NA, NB,SDA and SDB For culturing some bacteria and yeast, for bacteria the test organisms used were Methicillin resistant Staphylococcus aureus (MRSA), Streptococcus fecalis, Listeria monocytogenes, Bacillus subtilis, Escherichia coli, Enterobacterae rogense, Proteus mirabilis, pseudomonas fluorescence, Acinetobacter baumanni, Klebssiella pneumonia and Salmonella sp.For yeast the test organisms used were Candida tropical is, Candida albicans, and Candida Kruzi. Materials and methods: The growth rate of microbe’s strains in liquid media was investigated by measure the optical density at 600nm but the growth on solid media was indicated by the presence of microbial colonies. The viability of the bacteria and yeast was investigated by culturing every day after the preliminary period of incubation (24 hrs.) Results: The results showed that all bacteria grew in liquid media. Listeria monocytogenes, Escherichia coli, grew equal in both DPPG1 (0.83, 0.82) and NB (0.86, 0.82). Enterobacterae rogense and Pseudomonas fluorescence grew in DPPG1 (0.88, 1.12) and DPPG2 (0.81, 0.94) higher than in NB (0.59, 1.08), Klebssiella pneumonia showed good growth in both DPPG1andNB (0.91, 0.96).Candida albicans, and Candida Kruzi showed high growth in DPPG3 (1.16, 1.10).  The most tested organisms showed good growth on the solid alternative media, and still alive in 15 selected days in liquid media and showed noticeable growth on the solid media for selected 10 daysexcept the yeast C. tropical is that stops their growth on the seventh day on SDA. Discussion: The good growth indicates that DPPG extract possess sufficient amounts of nutrients for support the growth of microorganisms. Conclusion: The DPPG extract can be use efficaciously and economically for the cultivation of the bacteria and yeasts in place of high cost artificial media which used in the laboratories.Keywords: Culture media, Date palm pollen grains, Alternative nutrient sources, NA, NB, SDA, SDB, yeast, bacteria.